Kajian literatur: Dampak covid-19 terhadap pendidikan jasmani - Muhammad Syofian; Novri Gazali (Universitas Riau, 2021)
The research objective was to determine the impact of Covid-19 on physical education. This is very much needed to determine the implementation and impact of physical education learning during the Covid -19 pandemic which is currently still happening, with the hope that it can provide information on the methods used in literature studies or literature reviews. Literature study is a research design used in collecting data sources related to a topic. Data collection for literature studies was carried out using a database search tool as a stage of searching for literature sources. This data collection uses the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) method. The screening results that are appropriate and needed are 8 National Journal articles and 7 International Journal articles. Based on the articles that were found and analyzed, there were various impacts caused by the covid-19 virus. Among them are negative and positive impacts. The negative impact that occurs in the learning process is related to online learning techniques as well as the psychology of students, parents and educators who need adjustments in implementing learning methods. There are several positive impacts, namely education about information technology has increased drastically. There are new opportunities for academics to develop physical education and sports learning methods through distance learning models. Time to work from home is also relatively flexibleCopyright © The Author (s) 2021Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.